Let's solve your system by substitution.
3x−2y=−12;4x+5y=7
Step: Solve3x−2y=−12for x:
3x−2y=−12
3x−2y+2y=−12+2y(Add 2y to both sides)
3x= 2y−12
3 3
=
2y−12
3
(Divide both sides by 3)
x=
2
3 y−4
Step: Substitute
2
3
y−4 for x in 4x+5y=7:
4x+5y=7
4( 2/3 y−4)+5y=7
23
3
y−16=7(Simplify both sides of the equation)
23
3
y−16+16=7+16(Add 16 to both sides)
23
3
y=23
23
3 y
23
3 = 23
23
3
(Divide both sides by 23/3)
y=3
Step: Substitute 3 for y in x=
2
3 y−4:
x=
2
3 y−4
x= 2
3 (3)−4
x=−2(Simplify both sides of the equation)
Answer:
x=−2 and y=3 (underlined and / are fractions or division)